The interactive effects of remittances on economic growth and inequality in Western Balkan countries - Bajra, Ujkan Q. (Journal of Business Economics and Management, 2021)
Hardly any studies have investigated the impact of migrant remittances on economic growth (EG) and inequality in the Western Balkans as a whole (WB6). Using the method of instrumental variables (VI), the findings show that while remittances influence economic growth, their inflow also promotes a high level of migration and absorbs a large workforce by influencing the labor market and encouraging uncontrolled individual relocation. This paper also reveals that although remittances have eased income inequalities the share of remittances in a country’s economy has declined over the years. After testing for the endogeneity of remittances and controlling for various variables, the results indicate that migrant workers’ remittances do not provide strong support for economic growth and inequality. For the sample average, a 1-percent rise in the share of remittances in the economy (i.e., to GDP) will lead to a 0.10-percent rise in the economic cycle i.e. GDP growth, respectively will lead to a 0.05-percent drop in the share of people living in inequality. The findings also show that the interactive effect of remittances and foreign direct investment is lower on economic growth and inequality than the individual effect of each factor.